Sistem Informasi Inventaris Barang Berbasis Web Pada Dinas Kesehatan Kabupaten Gresik - Nurul Hafizah; Soffiana Agustin (Lembaga Pengembangan Kinerja Dosen, 2024)
The Gresik District Health Service, as one of the public service institutions in the health sector, has a big responsibility in providing quality health services for the community. In carrying out its duties, the Gresik District Health Service certainly cannot be separated from the need for inventory of goods. In reality, many government agencies, including health agencies, still manage inventory manually. Often, this method causes problems such as stock monitoring, asset tracking, and inefficient and inaccurate reporting. As a result, a solution is needed that can increase the efficiency and effectiveness of inventory management. Web-Based Goods Inventory Information System at the Gresik District Health Service with the aim of making it easier to process and report goods inventory data. This research applies a waterfall software development approach, which involves the stages of analysis, design, implementation and testing.